A business process and portfolio management approach for Industry 4.0 transformation. Issue 2 (28th December 2020) - Richard, Sophie; Pellerin, Robert; Bellemare, Jocelyn; Perrier, Nathalie
Abstract : Purpose: The purpose of this paper is to address the difficulties faced by manufacturing enterprises by providing a project portfolio management approach supporting the selection and prioritization of various Industry 4.0 projects where business process analysis is used to ensure the strategic alignment and value of the project portfolio. Design/methodology/approach: The design research methodology, a mixed applied research methodology, was used to develop and test the proposed approach. Findings: Despite the growing interest of the scientific and industrial communities in I4.0, it seems that there is no method by which manufacturing companies can select a large number of improvement projects. Moreover, studies tend to focus on the evaluation and implementation of a single technology, while the transformation of an intelligent plant requires the consolidation and coordination of many initiatives to achieve a global objective. Originality/value: The proposed project portfolio management model offers support to enterprises during their digital transformation and improves their processes by integrating technology levers through consistent and achievable selection of I4.0 initiatives while meeting strategic goals and objectives.